Bigdata of National Medicine Registers - Savosina, P.I.; Druzhilovskiy, D.S.; Filimonov, D.A.; Poroikov, V.V. (Biomedical Chemistry: Research and Methods, 2024)
Currently, various databases of approved drugs are widely used in the development and application of computer-aided drug design for training sets and validating predicted models. Most of the freely available databases contain information on a limited number of drugs. This leads to reduction in the space of pharmacotherapeutic chemistry studied and used by researchers. Information on drugs developed and used locally, in one or two countries, can be obtained from relevant national medicine registries. We have identified and analyzed registries from more than 70 countries around the world that are accessible through open web resources on the Internet. In addition to lists of approved therapeutics, many web resources offer the opportunity to review official documents published by medical authorities after the approval process. These documents contain a wide range of information about drugs, including data on structural formulations, pharmacodynamics and pharmacokinetics, toxicity, etc. The compounds represented in the registries, both in terms of quantity and structural diversity, exceed the known widely used databases of approved drugs. Combined data from national drug registries represent an example of “Big Data” in the biomedical field, taking into account all the difficulties involved in their processing. Its use in computer-aided drug design will not only expand the pharmacotherapeutic chemical space studied, but also improve the quality of the original data.